Antibacterial Activity Test of Cat's Whiskers Leaf Extract (Sauropus androgynus (L) Merr) Serum Preparation Against Propionibacterium acnes Bacteria - Maulina Nur Riskiani; Gigih Kenanga Sari; Maulita Saraswati (Pratama Medika : Jurnal Kesehatan, 2023)
One of the inflammatory diseases that occurs in the pilosebaceous unit is acne. One of the bacteria that causes acne is Propionibacterium acnes. Katuk leaves contain flavonoids, saponins, tannins and alkaloids which can be used as an acne treatment. One of the pharmaceutical preparations that can be used to treat acne is serum. The aim of this research is to formulate katuk leaf extract into a serum preparation, determine the physical quality characteristics of the serum preparation and then determine the antibacterial activity against Propionibacterium acnes.The research method used is experimental. Katuk leaves were extracted by maceration method with 70% ethanol then serum preparations were made with various extract concentrations, namely FI 40%, FII 60% and FIII 80% on the basis of serum xanthan gum. The physical quality test of the serum preparation including organoleptic, pH, homogeneity, spreadability, adhesion and viscosity was carried out, then the antibacterial activity test of Propionibacterium acnes was carried out with positive control of clindamycin 10 µg/disk, negative control of 5% DMSO using disc diffusion method. The results of this study indicate that the formula has a semi-solid form, the color of FI is brownish green, FII is dark green and FIII is blackish green with a distinctive aroma of the extract, the formulation is homogeneous, has a pH, spreadability, adhesion and viscosity that meets the requirements of a good serum. The results of the antibacterial activity test showed that the negative control had no inhibition zone, the positive control showed a strong inhibition zone of 20.09 and the katuk leaf extract serum formulation had a moderate inhibition zone of FI 18.11, FII 19.21 and FIII 19.36 the greater the inhibition zone produced due to the higher concentration of the extract made. The results of statistical analysis of variations in extract concentrations showed significant differences in the inhibition zone based on One Way Anova statistical analysis (p<0.05).